The First Isolation and Molecular Characterization of Shiga Toxin-Producing Virulent Multi-Drug Resistant Atypical Enteropathogenic Escherichia coli O177 Serogroup From South African Cattle - Montso, Peter Kotsoana; Mlambo, Victor; Ateba, Collins Njie (Frontiers in Cellular and Infection Microbiology, 2019)
Atypical enteropathogenic E. coli (aEPEC) is a group of diarrhoeagenic Escherichia coli with high diversity of serotypes, which lack the bundle-forming pili (BFP) and genes encoding for shiga toxins. The aim of this study was to isolate, identify and determine virulence and antibiotic resistance profiles of aEPEC O177 strains from cattle faeces. A total of 780 samples were collected from beef and dairy cattle and analysed for the presence of E. coli O177. One thousand two hundred and seventy-two (1272) presumptive isolates were obtained and 915 were confirmed as E. coli species. Three hundred and seventy-six isolates were positively confirmed as E. coli O177 through amplification of rmlB and wzy gene sequences using multiplex PCR. None of these isolates harboured bfpA gene. A large proportion (74%) of the isolates harboured hlyA gene while 55.6%, 47.6%, 35.9%, 8.1% and 1.9% possessed stx2, stx1, eaeA, stx2a and stx2d, respectively. Furthermore, 32.7% of the isolates harboured both stx1 and stx2 whereas 30.1% possessed stx1/stx2/hlyA genes. A small proportion (17.6%) of the isolates harboured all the four major virulence genes (stx1/stx2/hly/eaeA) targeted. Interestingly, one isolate harboured stx1/stx2/hly/eaeA/stx2a/stx2d, simultaneously. Further analysis revealed that the isolates displayed varied percentage antimicrobial resistances to erythromycin (92.3%), ampicillin (21%), tetracycline (9.6%), streptomycin (8.2%), kanamycin (2.1%), chloramphenicol (0.5%) and norfloxacin (0.3%). Moreover, 37(9.8%) of the isolates exhibited different phenotypic multi-drug resistance patterns. All 73(100%) isolates harboured at least one antimicrobial resistance gene. The aadA, streA, streB, erm and tetA resistance genes were detected separately and/or concurrently in 79.5%, 52.1%, 56.2%, 50.7% and 42.7% of the isolates, respectively. In conclusion, our findings indicate that environmental isolates of aEPEC O177 strains obtained from cattle in South Africa harboured virulence and antimicrobial resistance gene determinants similar to those reported in other shiga-toxin producing E. coli strains and suggest that these determinants may contribute to the virulence of the isolates.